In Memory of Natalia Kovalenko, a Director of the Acad. Filatov Museum and Exhibition Complex (Ukrainian Journal of Ophthalmology, 2025)
Natalia Borisovna Kovalenko was a Director of the Acad. Filatov Museum and Exhibition Complex, President of the de Ribas Foundation for Renewal of Odesa, Magister of International Cultural Studies Academy, and Member of the National Union of Journalists and National Union of Theater Workers. She graduated from Odesa Theater and Art High School Actor’s Department in 1965, and Kharkov Art Institute in 1982, and was a leading actress at the Pushkin Russian State Academic Theater at Kharkov, with 20 years of theatrical service.